(untitled) (Medico Legal Update, 2021)
Objective: The objective of this analysis was to assess serum islet cell anti-bodies concentrations and antiovarian anti-bodies in the relationship between the PCOS patient and the stable control group. Material and Method: In this study, 250 Iraqi women aged between 20-50 years were studied. The patients were divided into two groups: study group (n=125, PCOS women) and age-matched controls group (n=125 normal women). The blood sample was obtained on the 2nd day of menstruation cycle. Islet cells Ab and anti ovarian Ab concentrations were determined in both groups. Results: Women with PCOS had higher serum islet cell concentrations higher than control levels (p < 0.05). The levels of islet cells Ab and Anti-ovarian Ab were substantially positively associated with BMI, high levels of anti-mullerian hormone (AMH) and insulin resistance. Conclusion: The evidence from this study indicated that serum Islet cells Ab and anti-ovarian Ab levels in women with PCOS were observed to be higher compared with controls. Elevated serum Islet cells Ab and anti-ovarian Ab levels can be associated with high AMH and insulin resistance. Keywords: Islet cells, anti-ovarian Ab, anti-mullerian hormone, body mass index, polycystic ovary syndrome.